High Performance Cylindrical Capacitor as a Relative Humidity Sensor for Wearable Computing Devices. Issue 4 (16th February 2017) - Jang, Juhee; Han, Jeong In
Abstract : First, we designed and fabricated a cylindrical humidity sensing capacitor. In addition, we suggested its suitability as a capacitive RH sensor for wearable computing devices. Aluminum (Al) thin film for electrodes was uniformly deposited on a single fiber that consists of one fiber. The exposed area of the polyimide (PI) was particularly situated on an outer electrode to promote its moisture sensing capability. The capacitance change according to the relative humidity is indicated with a specific S-shape due to the interval adsorption reactions between the imide group and the water molecules. An adsorption mechanism is proposed based on the theory of the volume filling of micropores (TVFM), and the effect of PI thickness was investigated. In addition, the response times for adsorption and desorption were measured by changing the moisture condition. Moreover, with a repetitive bending test, the device durability was inspected by implementing the bending times and bending curvature radius.